CLASSIFICATION OF THE CONCEPT OF TIME ACCORDING TO THE FORMS OF MOVEMENT - Sultankulov Otabek; Zhalilova Jasminabonu (Western European Studies, 2024)
The article examines the types of time at the interdisciplinary level, including philology, philosophy and partly physics. There are different types of time: linear, cyclic, substantial and relational. The theories and research of various scientists, especially Newton and Leibniz, on the substantiality and relativity of time are analyzed. Russian Russian writers provide examples from various works related to time, as well as examples of expressions and phraseological units (expressions and phraseological units are given in three languages: Russian, English and Uzbek.)
Keywords: concept of time, substantiality; relativity; cyclicity